Kulturno prosvetno društvo Slovenski dom Zagreb (2020)
Slovenes living in Zagreb are assembling in Slovenski dom, a Cultural and Educational Society, the oldest association of Slovenes in Europe that has been operating interruptedly since 1929. It has survived four state formations, from the Kingdom of Yugoslavia to the Republic of Croatia. Various political situations dictated the ways and limitations of its functioning. The founder of the society, which was then named the National Library and Reading Room, was Dr Fran Zavrnik. Between the two World Wars, the activities of the association were very creative, it connected almost all Slovenes from Zagreb and their friends. During the Second World War, the authorities of the Independent State of Croatia banned its activities, nevertheless the spirit of friendship never died out, as the Slovenes in Zagreb helped their exiled compatriots. Due to occasional internal disagreements in the years after World War II, the Society experienced many ups and downs. After the disintegration of the of the former Socialist Federal Republic of Yugoslavia (SFRY), the association has focused its activities on realizing the idea of making Slovenski dom the home of all Slovenes in Zagreb. Today, the Society has about eight hundred members and in addition to its many activities, it is also engaged in publishing.
Some 10,000 Slovenes live in Croatia, mostly in Zagreb. They meet in Slovenski dom, the Cultural and Educational Association. It was established more than 90 years ago, in 1929, its founder was Dr Fran Zavrnik who was its first president. The Slovenski dom Zagreb association is the oldest society of Slovenes in Europe that has been operating without a break. Today, it has about 800 members. In addition to many activities, it also runs a rich publishing production. Since 1996, the society has been publishing the Novi odmev newsletter which, like most monographs, talks about activities of the Slovenian community in Croatia.